2012
DOI: 10.1097/sle.0b013e3182747b31
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intralesional Corticosteroid Injection in Endoscopic Treatment of Esophageal Strictures

Abstract: Intralesional triamcinolone presented a higher improvement of dysphagia and a lower refractority rate in patients with complex strictures with statistically significant differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Different steroids such as betamethasone or dexamethasone have been used intralesionally along with endoscopic dilation in other retrospective series with encouraging results [3,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different steroids such as betamethasone or dexamethasone have been used intralesionally along with endoscopic dilation in other retrospective series with encouraging results [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…The technique of dilation (either bougie or balloon) or injections (before or after dilation), as well as the performance of injections varies from only in the first session to as many sessions as the number of dilations [4,5,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The TNRD was comparable in 5 studies[ 17 , 18 , 19 , 20 , 21 ], where MD was -1.172 in comparison to the dilation alone group (95%CI: -0.238, 0.053; P = 0.057). The studies in this analysis showed no heterogeneity: ( Q = 3.66; df = 4; P = 0.45; I 2 = 0.0%).…”
Section: Resultsmentioning
confidence: 94%
“…However, the laceration developed in a patient, who continued the anticoagulant therapy during the procedure, and the other 4 patients received adjuvant chemotherapy, which is a risk factor for candidiasis. One perforation occurred in the dilation only group in Orive-Calzada et al[ 20 ] trial, with no complication reported in patients with intralesional steroid injection. Other trials did not report any adverse events in either therapy group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation